Search for scalar diphoton resonances in the mass range 65-600 GeV with the ATLAS detector in pp collision data at √s = 8 TeV - Aad, Georges; Anders, Christoph; Andrei, George Victor; Baas, Alessandra Edda; Brandt, Oleg; Colombo, Tommaso; Davygora, Yuriy; Dietzsch, Thorsten; Dunford, Monica; Giulini, Maddalena; Hanke, Paul; Jongmanns, Jan; et al. (Physical review letters, 2014)
A search for scalar particles decaying via narrow resonances into two photons in the mass range 65-600 GeV is performed using 20.3 fb−1 of √s=8 TeV pp collision data collected with the ATLAS detector at the Large Hadron Collider. The recently discovered Higgs boson is treated as a background. No significant evidence for an additional signal is observed. The results are presented as limits at the 95% confidence level on the production cross section of a scalar boson times branching ratio into two photons, in a fiducial volume where the reconstruction efficiency is approximately independent of the event topology. The upper limits set extend over a considerably wider mass range than previous searches.